The Effect Of Gender Diversity And Financial Expert On Accounting Quality In The USA - Wang, Xinyi (2019)
This research impresses the factors which affect the accounting quality for American companies, focusing on the influence of gender diversity and financial experts on the audit committee. The overarching aim of this study is to investigate the necessity of attaching more importance to gender diversity or the number of financial experts on the audit committee. Both the percentage of female directors and the board with at least three women are the tested variables which represent gender diversity. Moreover, this research separately tests the effect of the number of audit committee financial experts and the effect of the audit committee with at least two financial experts. This research uses two measurement methods to quantify accounting quality and establish four regression models to investigate the detailed hypotheses. The samples of 100 American companies for the period 2012-2018 are used in this study to draw empirical evidence. The findings confirm the positive correlation between the percentage of female directors and accounting quality for American firms. However, there no supporting evidence for the significant correlation between the board with at least three women and accounting quality. Moreover, both the number of financial experts or the audit committee with at least two financial experts show no correlation with accounting quality as well. This research contributes to both the accounting quality literature and the corporate governance literature by identifying the characteristic related to better accounting quality and the features unassociated with accounting quality. It could also make guidance for practice by questioning the importance of financial experts on the audit committee.